A differential shrinkage approach for evaluating particle formation behavior during drying of sucrose, lactose, mannitol, skim milk, and other solid-containing droplets. Issue 8 (11th June 2019) - Fu, Nan; Yu, Ming; Chen, Xiao Dong
Abstract: Particle formation process during drying of solid-containing droplets exerts profound influence on the property and quality of dried particles. A differential shrinkage approach is proposed to describe the particle formation behavior of different materials, by evaluating how the droplet shrinkage kinetics of the given material(s) deviates from the ideal shrinkage. Sucrose was selected as the reference material to establish ideal shrinkage kinetics, as its shrinkage at 10, 30, and 50 wt.% initial concentrations well followed the ideal shrinkage at all temperatures tested (70, 90, and 110 °C). Comparing the differential shrinkage kinetics of sucrose, lactose, and mannitol showed that mannitol has a strong crust-forming tendency, which could not be explained by the difference in the solubility of the three materials. By establishing a differential shrinkage curve for each material, this approach offers a straightforward and powerful method to evaluate the particle formation property of the material at various initial concentrations.